Development of a dual degree information system framework: A technology acceptance model - Muhammad Hafiz Aswad, Ahmad Kamal; Hamirahanim, Abdul Rahman; Suh, Jihae (Penerbit Universiti Malaysia Pahang, 2024)
Universiti Malaysia Pahang Al-Sultan Abdullah is a public higher education institution in Malaysia, which has been offering dual degree programs since 2010 in collaboration with various international higher education institutions across Germany, Kazakhstan, and China. Due to the complexity of dual degree students' data, the current internal management system can only record primary data. Thus, this study aims to design a prototype of an integrated management system that can handle the complexity of dual degree data. The prototype was developed using Microsoft Access based on the design science research methodology and two expert users conducted the user acceptance test to assess its functionality. The findings showed that the prototype had a major potential and was recommended for implementation in a real-world environment. This study contributes to the advancement of dual degree program management and highlights the importance of considering end-user feedback in system development and acceptance.